Morphometric variations of two patellid limpets between artificial breakwaters and natural reefs - Sempere Valverde, Juan (2024)
Artificial shorelines often differ from natural reefs in shape, composition, and habitat complexity. They promote higher accumulation of pollutants and increased physiological stress, which lead to changes in species distri butions and ecosystem functioning. This can promote trophic shifts and reduced genetic diversity of gastropod populations inhabiting artificial shorelines and might promote morphological changes, which may influence behaviour, vulnerability to predation, feeding efficiency, sex ratios, reproductive development, and overall fitness. This study explores inter- and intraspecific shell morphometric variations in Patella rustica and P. caerulea between breakwaters (ripraps) and natural reefs in three sites of Ceuta (North Africa, Spain), including a physicochemical assessment of the studied locations: shore orientation, inclination and wave exposure, and substratum nature, heterogeneity and roughness. Limpets on artificial substrata had a slightly smaller extra visceral cavity and flattened shell profile, which suggests that the desiccation and temperature stress driven by the lithological composition and roughness of the studied substrata might have influenced the registered shell shape variation. However, the high morphometric variation registered for both species across sites and substrata suggests that limpets’ morphology might be responding to a complex interaction of environmental and ecological factors rather than solely rock type. The findings of this study highlight the complex interplay between rock type and local environmental conditions in shaping patellid limpets’ shell morphology and provide insights into the adaptive mechanisms that drive shell shape variation in limpet populations in the face of coastal sprawl and anthropogenic global change.